UM CONCEITO DE EQUIVALÊNCIA NA EXPRESSÃO VERNÁCULA DA POESIA LATINA - Prado, João Batista Toledo (Organon, 2012)
Taking Joseph Brodsky’s concept of “equivalence” as far as translating foreign poems intoliterary forms plausible to the translator’s mother tongue and culture, this paper offers a possibleapplication of that concept to the latin love elegy lesser constituent unit, the elegiac couplet, and on theprosodic elements peculiar to the metres which it is made up of: the hexametre and the pentametre. Theintention here is to study the poetic nature of the latin love elegy, through the latin linguistic systemcharacteristics which provide the very basis for its metrical poetic system. That posture has driven us toa revaluation of the latin metric system through the prism of linguistic investigation, on all thatconcerns at least the elegiac couplet and its prosodic specificities, what has allowed to uncover anentire new range of possibilities to reading elegiac expressivity, as it was attempted to show with oneexemple taken from the roman elegiac poet Tibullus, from the century I b. C.